Electromagnetic Analysis of an Axially Periodic Disk-Loaded Slow-Wave Structure with Low-Loss Dielectric Filling between Disks for a Magnetically Insulated Line Oscillator - Upadhyay N.; Kumar A.; Tripathi P.; Dwivedi S. (My University, 2025)
The partially dielectrically filled periodic disk-loaded co-axial structure as a slow wave interaction structure for magnetically insulated transmission line oscillator (MILO) has been electromagnetically analyzed using field matching technique. The slow wave structure (SWS) includes a periodic disk-loaded coaxial structure in which the low-loss dielectric material is partially filled between successive disks. In the analysis, the dispersion relationship and interaction impedance have been calculated taking into account all the harmonics generated inside the structure. The effect of the dielectric constant of the material on the dispersion characteristics and phase velocity has been investigated. Also, the effect of different structural parameters on the dispersion characteristics and the interaction impedance has been obtained. To validate the performed theoretical analysis, the analytically obtained dispersion results have been compared with previously known dispersion results and then also confirmed by the commercial code 'Computer Simulation Tool (CST) Studio Suite.' The agreement between theoretical analysis and simulation with respect to the dispersion characteristics is within 5%. © 1973-2012 IEEE.